2018
DOI: 10.5607/en.2018.27.6.593
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tetrodes Coated with Au Nanoparticles (AuNPs) and PEDOT and Their Application to Thalamic Neural Signal Detection in vivo

Abstract: Tetrodes, consisting of four twisted micro-wires can simultaneously record the number of neurons in the brain. To improve the quality of neuronal activity detection, the tetrode tips should be modified to increase the surface area and lower the impedance properties. In this study, tetrode tips were modified by the electrodeposition of Au nanoparticles (AuNPs) and dextran (Dex) doped poly (3,4-ethylenedioxythiophene) (PEDOT). The electrochemical properties were measured using electrochemical impedance spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The obtained CFE/GO electrode was subjected to potentiostatic electrochemical reduction in 140 mM NaCl solution (parameter: voltage, −0.9 V; time, 200 s), thus producing a CFE/ERGO electrode. EDOT (2 mg/mL, dissolved in acetonitrile) was electropolymerized onto the CFE/ERGO electrode using the CV method (parameter: potential range, −0.2 to 1.6 V; scan rate, 1 mV/s; cycles, 5–20), denoted as a CFE/ERGO/PEDOT electrode. Followed by potentiostatic electrochemical oxidation treatment in 140 mM NaCl solution (parameter: voltage, 2.0 V; time, 25–400 s), CFE/ERGO/PEDOT gave birth to a CFE/EOGO/PEDOT electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained CFE/GO electrode was subjected to potentiostatic electrochemical reduction in 140 mM NaCl solution (parameter: voltage, −0.9 V; time, 200 s), thus producing a CFE/ERGO electrode. EDOT (2 mg/mL, dissolved in acetonitrile) was electropolymerized onto the CFE/ERGO electrode using the CV method (parameter: potential range, −0.2 to 1.6 V; scan rate, 1 mV/s; cycles, 5–20), denoted as a CFE/ERGO/PEDOT electrode. Followed by potentiostatic electrochemical oxidation treatment in 140 mM NaCl solution (parameter: voltage, 2.0 V; time, 25–400 s), CFE/ERGO/PEDOT gave birth to a CFE/EOGO/PEDOT electrode.…”
Section: Methodsmentioning
confidence: 99%
“…One way to circumvent this problem is the use of rough electrode materials that provide a large electrochemically active surface area on minimal geometrical dimensions. , Thereby, it is possible to reduce the geometrical size of an electrode contact while retaining the preferential electrochemical properties of a large electrode. Various versions for such materials have been suggested in the literature, expanding from micro- and nanostructured metals over carbon-based materials to conducting polymers. Most roughening methods, however, require rather complex processes (e.g., sputter deposition for IrOx or laser roughening for Pt), suffer from limited mechanical stability or toxicity (e.g., for Pt-Black ), or are prone to delaminate (e.g., for conducting polymers), restricting their use in long-term applications. Thanks to their ease of fabrication, electrolyte-based (electro)­chemically deposited platinum coatings have gained special attention as rough electrode materials for neural implants. , While impedance reduction is well documented for these coatings, other important electrode parameters such as biocompatibility, longevity, mechanical stability, and stimulation performance remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrodes are useful tool for neural recordings, and many studies have reported that coatings on the surfaces of tetrodes can efficiently improve the probability of detecting neural signals. Some studies have shown the beneficial effects of AuNPs and PEDOT separately as separate coating materials [6,16,33,48]. However, the aim of this study was to demonstrate the possibility of electroplating PEDOT additionally onto AuNPs-coated bare wires.…”
Section: Discussionmentioning
confidence: 93%
“…Au nanoparticles (AuNPs) are well-known materials that are non-toxic, highly conductive and biocompatible [18]. AuNPs are widely used in the field of biosensors, multielectrode arrays (MEAs), and microelectrodes [19][20][21]. MEAs with electrodeposited AuNPs have been reported to possess increased surface area and improved recording performance in vitro [19].…”
Section: Characterization Of Tetrodes Coated With Au Nanoparticles (Aunps) and Pedot And Their Application To Thalamic Neural Signal Detementioning
confidence: 99%
See 1 more Smart Citation